Changing Gellerup Park: Political Interventions and Aesthetic Engagement in an Exposed Social Housing Area in Denmark - Eriksson, Birgit; Nielsen, Anne Mette W. (The Nordic Journal of Aesthetics, 2022)
Some low-income social housing neighborhoods are undergoing radical transformations in Denmark. Classified as “ghettos” and “parallel societies,” and marked by area-specific legislation, we identify a triple exposure in these neighborhoods. The residents are exposed to inequality, stigmatization, and discriminatory inter-ventions. Parallel to this, cultural policies and programs have ap-proached these same neighborhoods based on the assumption that they can be “elevated” through art. Drawing upon a broader re-search in art project in four social housing areas (Eriksson, Nielsen, Sørensen and Yates, 2022), this article focuses on Gellerup Park in Aarhus and considers how two site-specific art platforms address the site and time-specific conditions of the area, offering alterna-tive relations and forms of engagement.